Combining cognitive bias modification training (CBM) and transcranial direct current stimulation (tDCS) to treat binge eating disorder: study protocol of a randomised controlled feasibility trial. Issue 10 (22nd October 2019) - Gordon, Gemma; Brockmeyer, Timo; Schmidt, Ulrike; Campbell, Iain C
Abstract : Introduction: Binge eating disorder (BED) is a common mental disorder, closely associated with obesity. Existing treatments are only moderately effective with high relapse rates, necessitating novel interventions. This paper describes the rationale for, and protocol of, a feasibility randomised controlled trial (RCT), evaluating the combination of transcranial direct current stimulation (tDCS) and a computerised cognitive training, namely approach bias modification training (ABM), in patients with BED who are overweight or obese. The aim of this trial is to obtain information that will guide decision-making and protocol development in relation to a future large-scale RCT of combined tDCS+ABM treatment in this group of patients, and also to assess the preliminary efficacy of this intervention. Methods and analysis: 66 participants with Diagnostic and Statistical Manual-5 diagnosis of BED and a body mass index (BMI) of ≥25 kg/m 2 will be randomly allocated to one of three groups: ABM+real tDCS; ABM+sham tDCS or a wait-list control group. Participants in both intervention groups will receive six sessions of ABM+real/sham tDCS over 3 weeks; engaging in the ABM task while simultaneously receiving bilateral tDCS to the dorsolateral prefrontal cortex. ABM is based on an implicit learning paradigm in which participants are trained to enact an avoidance behaviour in response to visual food cues. Assessments will be conducted at baseline, post-treatment (3 weeks) and follow-up (7 weeks post-randomisation). Feasibility outcomes assess recruitment and retention rates, acceptability of random allocation, blinding success (allocation concealment), completion of treatment sessions and research assessments. Other outcomes include eating disorder psychopathology and related neurocognitive outcomes (ie, delay of gratification and inhibitory control), BMI, other psychopathology (ie, mood), approach bias towards food and surrogate endpoints (ie, food cue reactivity, trait food craving and food intake). Ethics and dissemination: This study has been approved by the North West-Liverpool East Research Ethics Committee. Results will be published in peer-reviewed journals. Trial registration number: ISRCTN35717198